2015
DOI: 10.1039/c4tc02584a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient photochemical upconversion in a quasi-solid organogel

Abstract: Photochemical upconversion in a quasi-solid gel proceeds with an identical efficiency to an otherwise identical liquid composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 50 publications
2
79
0
Order By: Relevance
“…It was shown that the upconverted fluorescence intensity was highly dependent on the temperature and decreased dramatically below the glass transition temperature ( T g ) of the polymer . This result suggested that translational and rotational mobility of the chromophores is essential for efficient upconversion in solid materials with low chromophore content, as the influence on the various energy transfer steps that are involved in the TTA‐UC process is significant . It was later hypothesized that an increase of the UC chromophore concentrations in the matrix could change this situation by way of enabling energy transfer on account of small intermolecular distances and, thus, increase the efficiency of TTA‐UC process in the solid state .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the upconverted fluorescence intensity was highly dependent on the temperature and decreased dramatically below the glass transition temperature ( T g ) of the polymer . This result suggested that translational and rotational mobility of the chromophores is essential for efficient upconversion in solid materials with low chromophore content, as the influence on the various energy transfer steps that are involved in the TTA‐UC process is significant . It was later hypothesized that an increase of the UC chromophore concentrations in the matrix could change this situation by way of enabling energy transfer on account of small intermolecular distances and, thus, increase the efficiency of TTA‐UC process in the solid state .…”
Section: Introductionmentioning
confidence: 99%
“…Standard spin statistics predict an efficiency of 1/9 for TTA, but usually the efficiency of TTA is higher because the high-energy quintet states are not accessible. Φ TTA is 0.52 for DPA 40,41 and 0.33 for rubrene. 42 Third, molecules with high PL QYs meet the requirements for sensitizers, such as the PL QYs of 0.90 for DPA 43,44 and 0.98 for rubrene.…”
mentioning
confidence: 99%
“…This gel Φ UC >0.6 and 14% under ambient and oxygen‐free conditions, respectively. Schmidt and co‐workers also reported UC in a supramolecular tetralin organogel made of 1,3:2,4‐bis(3,4‐dimethylbenzylidene) sorbitol (DMDBS) and containing the UC pair palladium tetraphenylporfirin and DPA . In this case, identical TTA‐UC efficiency in the gel sample and in a comparable liquid composition was observed (Φ TTA = 0.07), with the advantage of better processability for the former in terms of potential device applications.…”
Section: Photon Upconversionmentioning
confidence: 86%